Lead Ion Removal in Water Using Low Methoxy Pectin-Guar Gum Beads Hybrid Adsorbent - Subroto, Nadya Nursidah Pratiwi; Tarmidzi, Fadhil Muhammad; Wati, Ina; Armans, Velia Mulya (Indonesian Journal of Chemical Research, 2022)
A high level of lead in the sediment will cause contamination of aquatic biota. Lead pollutants in water may be treated by an easy and common adsorption process. A combination of both environmentally friendly and renewable materials, low methoxy pectin (LMP), and guar gum as adsorbents can reduce the need of activated carbon which requires high temperatures in its synthesis process. LMP was prepared from high methoxy pectin using a demethylation process under alkaline conditions. LMP and guar gum are diluted in 1 M calcium chloride as a crosslinking agent. The degree of esterification was carried out to determine the demethylation process. Adsorption of lead was carried out with a lead concentration of 165 ppm in acidic conditions for 24 hours. Lead concentration was measured using AAS. Results show that the optimal pH for demethylation was 12. The ratio of 1:2 pectin-guar gum produces the strong beads related to more O-H bonds in guar gum that can be developed. pectin-guar gum beads can adsorb 63% of lead at pH 6 due to the development of hydro-complex metal ions under more basic conditions.